AN EMPIRICAL EXAMINATION OF THE RELATIONSHIPS AMONG CREATIVITY, THE EVALUATION OF CREATIVE PRODUCTS, AND COGNITIVE STYLE AMONG CHINESE UNDERGRADUATES - Kuan-Chen Tsai (International Journal of Cognitive Research in Science, Engineering and Education, 2018)
The current study investigates creativity from a creative product perspective. More specifically, we want to know if a connection exists between an individual’s creativity and his or her evaluation of creative products. We also want to know what role cognitive style plays in this relationship. The sample (139 second-year undergraduates) was collected from an art and design program of an institution in Macau. Convenience sampling was used for the current study. The present study found partial support for the associations between cognitive style, creativity, and evaluations of creative products. Based on zero-order correlations, visual and verbal cognitive styles were moderately and positively correlated to three components of CPSS (novelty, resolution, and elaboration and synthesis). The results of the SEM further confirm this relationship between cognitive style and CPSS (r = .69, p < .05).